Balinese Women’s Strategy for Managing Waste Banks: Adaptation of Digital Technology for Business Sustainability in Denpasar City and Gianyar Regency, Province of Bali - Pramitha Purwanthi, Putu Ayu; Purwanti, Putu Ayu Pramitha; Yudha, I Made Endra Kartika; Mustika, Made Dwi Setyadi (Prospect Publishing, 2024)
ABSTRACT Bali is the third largest waste producing province in Indonesia compared to other provinces in Indonesia. Most waste bank managers are women who are members of community and traditional organizations. The problem that exists is that the potential and condition of waste banks are not properly identified so that many do not receive the government's attention, so their sustainability is threatened. The aim of this community service is to map the condition and potential of waste banks in two locations, namely Denpasar City and Gianyar Regency. The service method is in the form of FGD with women who manage waste banks. Based on the results of the FGD, the conditions, constraints and hopes of waste bank managers were formulated. The next conclusion is that women managing waste banks still do not fully know and have access to the use of digital technology to improve the sustainability of waste banks. A strategy that can be implemented is to increase socialization and assistance to women who manage waste banks. Key words: women, waste bank; digital technology; sustainability